Art what is itn why is itn - Canaday, John Edwin 1907- (Encyclopedia Britannica Films, 1962)
John Canaday analyzes the place of art among the humanities, as an expression of man's attempt to define what it means to be a human being. The program shows how the masterworks of art and architecture have formed a visual history of man's thought, ideals, and most widely held beliefs.